MORTALITY, REMOVAL, AND DISCARDED RATES IN BROILERS OF TWO GENETIC LINES - Francia M., María (2009)
The present work evaluated the mortality, removal, and discarded rates in broilers of two commercial genetic lines, reared in three consecutive cycles of 45-49 days each under similar management conditions. In each cycle, 360 birds per genetic line (A and B) were used. Necropsy was carried out to dead and removed birds. Removed birds were those that showed severe growth delay and discarded birds were those that showed injuries or abnormalities at the end of the cycle. In both lines, the main causes of mortality were the ascites syndrome and sudden death syndrome. Line B showed higher mortality rate during the first cycle (p<0.05), but there was no statistical difference in the removal and discarded rates between the two genetics lines. The main cause for removing birds in both lines was leg problems, mainly chondrodystrophia. In general, it can be concluded that productive performance in terms of mortality, removing and discarding birds was similar between both genetic lines.